1995
DOI: 10.1007/bf00294806
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic stress induces deposition of amyloid ? immunoreactivity in human brain

Abstract: The histoblot immunostaining technique for locating and characterizing amyloidogenic proteins was used to obtain information about the relationship of cerebral ischemia/hypoxia to the accumulation of amyloid beta protein (A beta). We investigated brains of 131 subjects (ages 25-94 years, mean 72 years). Three distribution patterns of A beta immunoreactivity were identified: (1) colocalization with diffuse and neuritic plaques of Alzheimer's disease (AD) and aging; (2) diffuse punctuate deposits in the cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0
5

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(128 citation statements)
references
References 22 publications
2
121
0
5
Order By: Relevance
“…[4][5][6][7][8][9] Although human studies have also indicated that soluble parenchymal amyloid precursor protein and β-amyloid 1 to 42 (Aβ ) accumulate in patients with multi-infarct dementia, 10,11 there are animal studies examining neurodegenerative mechanisms and cognitive impairment in global and focal experimental ischemia. Changes in neurotransmitter systems, trophic factors, and cell signaling and neuroinflammatory mechanisms have been well documented.…”
Section: Evidence From Experimental Studiesmentioning
confidence: 99%
“…[4][5][6][7][8][9] Although human studies have also indicated that soluble parenchymal amyloid precursor protein and β-amyloid 1 to 42 (Aβ ) accumulate in patients with multi-infarct dementia, 10,11 there are animal studies examining neurodegenerative mechanisms and cognitive impairment in global and focal experimental ischemia. Changes in neurotransmitter systems, trophic factors, and cell signaling and neuroinflammatory mechanisms have been well documented.…”
Section: Evidence From Experimental Studiesmentioning
confidence: 99%
“…In a postmortem study of 131 brains, the investigators found punctate A␤ deposits in the cerebral cortex in association with small vessel cerebral vascular disease and other ischemic-susceptible zones, such as arterial border zones. 4 This has been further supported in several rat models in which acute occlusion of the middle cerebral artery has been accompanied by both increased amyloid precursor protein (APP) and A␤ immunoreactivity in the "penumbral region" of infarct 1 week later. 1,2 It has been suggested that this local ischemic effect on A␤ accumulation may relate to an upregulation and alteration of APP processing favoring beta and gamma peptide pathways, with increased ␤-secretase activity observed in rats after induced transient ischemic attack.…”
Section: Patterns Of Focal Pib Retentionmentioning
confidence: 88%
“…Recent animal and human studies assessing the association between cerebral amyloid and brain ischemia also have been conflicting. [1][2][3][4] N-methyl-[11C]2-(4Ј-methylaminophenyl)-6-hydroxybenzothiazole ( 11 C-PiB) is a derivative of thioflavin-T and has been developed as a ligand for imaging cerebral ␤-amyloid (A␤). 5 Positron emission tomography (PET) has been successfully used to detect and quantify A␤ deposition in the living human brain, in AD, other dementias, and cerebral amyloid angiopathy-related hemorrhage.…”
mentioning
confidence: 99%
“…As might be expected given the harsh treatment of the tissue, the method lacks fine resolution, but it does illustrate the general distribution of pathologic forms of α-synuclein without the confound of normal cellular α-synuclein, which is very abundant in synaptic termini in the neuropil of gray matter. The approach is not novel and has also been used to show abnormal forms of β-amyloid in human brains after ischemic stress (12). This is, however, the first use of a modification of histoblots to detect abnormal forms of α-synuclein.…”
Section: Histoblots Detect Protease-resistant Proteinmentioning
confidence: 99%